2019
DOI: 10.1007/s10549-018-05119-2
|View full text |Cite
|
Sign up to set email alerts
|

Re-testing of predictive biomarkers on surgical breast cancer specimens is clinically relevant

Abstract: Purpose The accuracy of predictive and prognostic biomarker assessment in breast cancer is paramount since these guide therapy decisions. The aim was to investigate the concordance of biomarkers and immunohistochemical (IHC)-based surrogate tumor subtypes between core needle biopsies (CNB) and consecutive paired breast cancer surgical resections. Methods This retrospective study comprised two cohorts of patients with primary breast cancer diagnosed between 2016 and 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 46 publications
4
43
1
3
Order By: Relevance
“…Identifying HER2-positive breast cancer patients by CNB is important, as neoadjuvant HER2-targeted therapy is an effective option for these patients. In this study, the CR for HER2 status, as determined by HER2 IHC or reflex HER2 SISH, was as high as 99.7% (kappa, 0.988), which was higher than most previous reports (ranging from 61%-97.3%) [10,[18][19][20][21][22][23][24][25][26][27][28][29]. The reason for this high CR could partially be due to performing reflex HER2 SISH for all HER2 IHC equivocal cases to determine final HER2 status strictly following ASCO/CAP guidelines.…”
Section: Discussioncontrasting
confidence: 57%
“…Identifying HER2-positive breast cancer patients by CNB is important, as neoadjuvant HER2-targeted therapy is an effective option for these patients. In this study, the CR for HER2 status, as determined by HER2 IHC or reflex HER2 SISH, was as high as 99.7% (kappa, 0.988), which was higher than most previous reports (ranging from 61%-97.3%) [10,[18][19][20][21][22][23][24][25][26][27][28][29]. The reason for this high CR could partially be due to performing reflex HER2 SISH for all HER2 IHC equivocal cases to determine final HER2 status strictly following ASCO/CAP guidelines.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies reported varying concordance of results between the surgical specimen and core needle biopsy of ER (77.8 to 99%), PR (69 to 97%), and HER2 (64 to 97%), respectively, with particular emphasis placed on a general tendency for higher discrepancies in PR status [22][23][24][25][26][27]. In addition to substantial improvement in receptor measurement accuracy, interlaboratory variation still exists in the assignment of receptor status [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…I want to congratulate Robertson and their colleagues for their article [1] in which they investigated the concordance of biomarkers and immunohistochemical (IHC)-based surrogate tumor subtypes between core needle biopsies (CNB) and consecutive paired breast cancer surgical resections. This retrospective study comprised two cohorts of patients with primary breast cancer: one treated with primary surgery (n = 526) and one with neoadjuvant chemotherapy (NAC) (n = 216).…”
Section: Dear Editormentioning
confidence: 99%